2007
DOI: 10.1038/nature05736
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylation regulates kainate-receptor-mediated synaptic transmission

Abstract: The small ubiquitin-like modifier protein (SUMO) regulates transcriptional activity and the translocation of proteins across the nuclear membrane. The identification of SUMO substrates outside the nucleus is progressing but little is yet known about the wider cellular role of protein SUMOylation. Here we report that in rat hippocampal neurons multiple SUMOylation targets are present at synapses and we show that the kainate receptor subunit GluR6 is a SUMO substrate. SUMOylation of GluR6 regulates endocytosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
300
4
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 252 publications
(322 citation statements)
references
References 28 publications
(36 reference statements)
8
300
4
4
Order By: Relevance
“…It is reported that GluK2 is SUMOylated by SUMO1 at the C-terminal K886 residue in response to kainate stimulation. SUMOylation of GluK2 is required for agonist-induced endocytosis of GluK2-containing kainate receptors and is involved in the regulation of synaptic transmission [11]. In this study, we report enhanced conjugation of GluK2 by SUMO1 following global brain ischemia.…”
Section: Introductionmentioning
confidence: 57%
“…It is reported that GluK2 is SUMOylated by SUMO1 at the C-terminal K886 residue in response to kainate stimulation. SUMOylation of GluK2 is required for agonist-induced endocytosis of GluK2-containing kainate receptors and is involved in the regulation of synaptic transmission [11]. In this study, we report enhanced conjugation of GluK2 by SUMO1 following global brain ischemia.…”
Section: Introductionmentioning
confidence: 57%
“…La sumoylation participe à la régulation de nombreuses voies de signalisation cellulaire et la dérégu-lation des mécanismes conduisant à la sumoylation des protéines a sans nul doute des conséquences importantes pour les fonctions neuronales. Il existe un grand nombre de protéines sumoylées au niveau de la synapse [17] mais leur nature et leur fonction restent à ce jour inconnues. L'identification de la fonction des substrats synaptiques de la sumoylation peut permettre de mieux comprendre le rôle joué par la sumoylation dans la régulation des fonctions synaptiques et par conséquent dans la physiologie du neurone.…”
Section: Discussionunclassified
“…L'enzyme de désu-moylation SENP5 est également importante pour la fission et le maintien de la morphologie mitochondriale [16]. Ces données, auxquelles s'ajoute l'identification de multiples substrats de la sumoylation dans les mitochondries cérébrales [17], laissent entrevoir un rôle prépon-dérant de cette modification dans l'homéostasie mitochondriale et le processus d'apoptose.…”
Section: Synthèse Revuesunclassified
See 2 more Smart Citations